(untitled) (Eurasian Journal of Philology Science and Education, 2019)
In the article it’s analysedthe development of the autobiographical genre in literature, which is of great importance when studying the works of the autobiographical genre in higher education. Knowledge of the history of the creation of a work contributes to a deeper understanding of the plot of the work being studied and brings students closer to the images of the characters. If in autobiographical works, some writers describe everythin that happened around, others repel from inside spiritual existence and tie up to researchihg of own thoughts and souls, through this they try to reflect the sate of mankind in general.